Peroxisomal Membrane Contact Sites in Yeasts - Joshi, Amit S. (Frontiers in Cell and Developmental Biology, 2021)
Peroxisomes are ubiquitous, single membrane-bound organelles that play a crucial role in lipid metabolism and human health. While peroxisome number is maintained by the division of existing peroxisomes, nascent peroxisomes can be generated from the endoplasmic reticulum (ER) membrane in yeasts. During formation and proliferation, peroxisomes maintain membrane contacts with the ER. In addition to the ER, contacts between peroxisomes and other organelles such as lipid droplets, mitochondria, vacuole, and plasma membrane have been reported. These membrane contact sites (MCS) are dynamic and important for cellular function. This review focuses on the recent developments in peroxisome biogenesis and the functional importance of peroxisomal MCS in yeasts.